CHARACTERISTICS OF SPEECH OF CHILDREN WITH SPEECH DEFICIENCY (Conference Zone, 2022)
This article presents an analysis of pedagogical and psychological literature on the problem of speech characteristics of children with dysarthria speech deficiency.